A Field Guide To The Reptiles Of South-East Asia - Das, Indraneil (Bloomsbury Publishing Plc, 2010)
This beautiful and indispensable handbook will appeal to the expert and amateur alike. Offering a wealth of information on identifying nearly 400 of the most commonly encountered garden wildlife in Britain and Northern Europe, each species is clearly described with informed and concise text and an easy-to-follow layout for quick identification. Detailed colour artworks accompany the accessible and engaging text, making this guide a wonderful addition to any book shelf.Other titles in "New Holland's The Wildlife Trusts" series are: "Guide to Garden Wildlife", "Birds", "Butterflies & Moths", "Insects", "Trees", and "Wild Flowers".